X-ray spectroscopy uncovering the effects of Cu and Fe based nanoparticles on Phaseolus vulgaris L. germination and seedling development - Duran, Nádia Marion (2018)
Nanotechnology offers a great potential do design fertilizers with unique properties capable to boost the plant productivity. However, the nanoparticles environmental fate and their toxic responses still need to be deeply investigated to their safe use. This study aims to investigate the effect of copper oxide (nCuO) and magnetite nanoparticles (nFe3O4) on the germination and seedling development of Phaseolus vulgaris L. Seeds were treated in nanoparticles dispersions in a wide range of concentrations (1, 10, 100 and 1 000 mg L-1) and incubated in a germination chamber during 5 days. Different sized nCuO (25, 40 and <80 nm) and polyethylene glycol (PEG) coated nFe3O4 were evaluated. Although both nCuO and nFe3O4 treatments did not affected the germination rate, seedling weight gain was promoted by 40 nm CuO at 100 mg Cu L-1 and inhibited by 1 000 mg Cu L-1 of 25 nm CuO and positive control (CuSO4). Among the tested nCuO, the higher chemical reactivity was found for the 25 nm CuO, and this may partially explain the observed deleterious effects. Seeds treated in nFe3O4-PEG at 1 000 mg Fe L-1 increased radicle elongation compared to the negative control (water), while Fe2+/Fe3+ (aq) (positive control) and bare nFe3O4 at 1 000 mg Fe L-1 treatments reduced the radicle of the seedlings. The growth promoted by the PEG-coated nanoparticles can be justified by the higher water uptake induced by the PEG, and also by its lower chemical reactivity compared to the bare nanoparticles. This was reinforced by enzymatic assays since nFe3O4-PEG treatment was also the least harmful to the alpha-amylase activity. X-ray fluorescence spectroscopy (XRF) showed that most of the Cu and Fe incorporated by the seeds remained in the seed coat, specially in the hilum region, and X-ray tomography indicated that Fe3O4-PEG penetrated in this structure. X-ray absorption spectroscopy (XAS) unraveled that the Cu and Fe chemical environment of the nCuO and nFe3O4-PEG treated seeds persisted mostly in its primitive form. These results contribute to the understanding of how nCuO, nFe3O4 and nFe3O4-PEG interact with common bean seeds and seedlings and highlights its potential use in seed priming